Anxiety among postgraduate students - Ismail, R. (Serials Publications, 2017)
Overcoming statistics anxiety is one of the main goals in statistics teaching. Previous researchers believed that statistics anxiety can only be reduced by developing and implementing appropriate effective intervention strategies. In order to be able to develop an effective strategy, the nature of statistics anxiety should be studied. Acknowledging the main factor would helps instructor to overcome anxiety. This paper investigates factors that influence the statistics anxiety among postgraduate students. The objectives for this study are (i) to determine significant differences between gender and statistics anxiety, (ii) to determine dominant factors of statistics anxiety, and (iii) to examine significant correlation between the factors and statistics anxiety among postgraduate students. The Statistics Anxiety Rating Scale (STARS) was administered and given to tertiary level students who take statistics courses. The data were analyzed using Statistical Package for the Social Science (SPSS) version 21.0. The result shows that there was no significant correlation between the factors and statistics anxiety influencing the highest anxiety when dealing with statistics in statistics courses. Therefore, reducing or overcoming students' anxiety and improving their attitude will enhance their value of statistics and further encourage their professional development in counseling profession.